Ecological Treatment of Urban Organic Waste in the Context of Climate Change- A Chinese Perspective - Li, Xiuhua; Khan, Mehran Idris; Chang, Yen-Chiang (International Journal of Management and Sustainability, 2019)
Climate change is a common challenge for human society. On December 12, 2015, as the Paris Agreement adopted, China’s carbon emission reduction actions have been more determined to become a fundamental force in promoting global climate governance. China has to carry on the corresponding reform in terms of the policy, technology, market of climate control, and innovate the way of low carbon development and energy transformation with Chinese characteristics. It will indicate that urban organic waste is closely related to the emission of greenhouse gas, which resources and ecological treatment will be faced with a profound change. Based on the analysis of the present situation and the development direction of China’s urban organic waste treatment, this paper will provide a way for the construction of the ecological treatment mechanism of urban organic waste in the context of climate change. To this end, this study adopts qualitative means of investigation, and takes a Beijing-based energy company as case study and draw lessons from its implications concerning the ecological treatment of urban organic wastes, for future considerations by various stakeholders including government agencies.